Pengaruh Inovasi, Promosi Dan Diversifikasi Produk Terhadap Peningkatan Nasabah Bank BRI Unit Candipuro - Putra, Jody Alfian; Febriyanto, Febriyanto (Jurnal Manajemen DIVERSIFIKASI, 2022)
Jody Alfian Putra, 2021 "The Influence of Innovation, Promotion and Product Diversification on Increasing Customers of Bank BRI Candipuro Unit". Faculty of Economics and Business, University of Muhammadiyah Metro. Supervisor: (1) Dr. H. Febriyanto, S. E., M. M and Supervisor (2) Nani Septiana, S. E., M. M. This study aims to determine the effect of innovation, promotion and product diversification on increasing customers of the BRI Unit Candipuro bank. By distributing questionnaires in the form of questions about innovation, promotion and product diversification to increase customers. Then processed with SPSS version 22 with the classical assumption test approach with the methods of normality, linearity, homogeneity. This study uses quantitative methods with multiple linear regression analysis, partial test, F test, determination to determine the effect of innovation, promotion and product diversification on increasing customers of BRI Bank Candipuro Unit. The results showed that simultaneously innovation, promotion and product diversification. Partial research shows that innovation has a positive and significant effect, promotion has a positive and significant effect and product diversification has a positive and significant effect on increasing customers. Keywords: Innovation, Promotion, Product Diversification, Customer Improvement